Newborn care practices in Nilphamari District of Bangladesh after a year of maternal, neonatal and child health intervention - Choudhury, Nuzhat; Hashima-E-Nasreen (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to describe newborn care practices in an area where maternal, neonatal and child health (MNCH) intervention is being implemented, and to assess the effect of such intervention on newborn care. A cross sectional survey was carried out on 600 mothers to describe newborn care practices in Nilphamari district of Bangladesh. Logistic regression was used to identify socio-demographic, ante-natal and delivery care factors that were associated with newborn care practices. Mothers who had at least three ante-natal care visits had significantly better newborn care practice. Likewise, the presence of an individual trained in newborn care management was significantly associated with better newborn care. The association between 'newborn care practices' with 'ante-natal care visits' and 'presence of trained person in delivery' suggests that evidence-based newborn care practices can be promoted through community-based health worker with existing health services.